RETRACTED: Sports-oriented physical education as a central element of the model of environmental worldviews, ethics, and sustainability of deviant adolescents - Bayer Elena; Gadarova Svetlana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001